Efisiensi Alokatif Usaha Tani Paprika di Kecamatan Cisarua - Cika Santi Hidayanti; Hastuti Hastuti (Jurnal Ilmu Pertanian Indonesia, 2023)
Cultivation of bell peppers by farmers in Pasirlangu Village, Cisarua District, West Bandung Regency, tends to reach less optimum production, indicated by the average production per crop. The purpose of this study is to evaluate three aspects: (1) factors that affect productivity, (2) allocative efficiency, and (3) income of paprika farming in Pasirlangu Village. The Ordinary Least Squares method was used to analyze factors affecting productivity, the Marginal Product Value method to assess allocative efficiency, and the R/C ratio to calculate cultivation profits. The results showed that labor and seed inputs are inputs that have a significant effect on the productivity of agricultural businesses. In the efficiency analysis, seed input and husk charcoal are not efficient inputs, so these inputs need to be added. The income analysis shows that the paprika farming business in Pasirlangu Village is still profitable even though it is not optimal, as indicated by the ratio of profits and costs, which is > 1. Keywords: bell pepper, income analysis, marginal product value, ordinary least squares, R/C ratio